Decomposing multiple β‐diversity reveals non‐random assembly of the waterbird communities across anthropogenic subsidence wetlands. (9th August 2021) - Li, Chunlin; Wang, Xue; Zhang, Baowei; Cui, Peng; Feng, Gang; Svenning, Jens‐Christian
Abstract: Aim: Understanding how biotic communities are spatially distributed is essential for biodiversity conservation in human‐modified landscapes. The large‐scale subsidence wetlands generated by underground coal mining in China have been increasingly used by large numbers of waterbirds, which remain understudied. We aimed to explore the role of non‐random assembly in shaping the regional waterbird diversity in non‐breeding seasons, providing insights for the conservation. Location: The North China Plain. Methods: Taxonomic β‐diversity and functional β‐diversity (both multiple‐site and pairwise) of the waterbird communities were quantified and decomposed into turnover (i.e. species replacement) and nestedness components (i.e. the poorer sites being subsets of the richer sites). Observed functional α‐diversity and pairwise β‐diversity, as well as the two components, were compared with simulated means under random assembly processes in null models, which maintained the species richness, pairwise taxonomic dissimilarity, and its turnover and nestedness components as the observed. Results: The communities exhibited similar multiple‐site taxonomic and functional β‐diversity, which were primarily contributed by taxonomic and functional turnover, respectively. The pairwise functional β‐diversity, as well as its turnover and nestedness components, was positively correlated with their taxonomic counterparts. The pairwise functional β‐diversity was higher than the taxonomic β‐diversity, with the former mainly reflecting nestedness of functional strategies and the latter reflecting species replacement. The observed functional α‐diversities in most communities were lower, and most of the observed pairwise functional β‐diversities were higher than the simulated means in null models. Main conclusions: The above patterns suggest the existence of non‐random assembly of the waterbird communities across the subsidence wetlands. To protect waterbirds in the subsidence wetlands, we suggest that most wetlands should be protected via increasing habitat diversity. Furthermore, considering the changing environmental conditions, changes in the multiple biodiversity metrics should be monitored to inform the ongoing management plans.